A review of technological platforms for the development of mathematical competences available to students of the AITEC higher technological institute - Chéquer Bajaña, Diana; Castillo Cedillo, Zaida (Revista Minerva, 2023)
Being current education a paradigm for future generations, technology can be mentioned as an advance to science both in teaching and learning at all educational levels, mainly in higher education where processes are even more complex in these virtual environments. The objective of this article is the bibliographic study of the different technological resources for the development of mathematical competences in the students of the Admiral Illingworth Higher Technological Institute, for a lasting learning and also for the teacher a successful teaching. The methodology used in this article, both bibliographic and the direct observation technique carried out by the authors, leads to the conclusion about higher education and the importance of promoting these methods through the use of technological tools that transfer to perpetual learning.
Keywords: Technological resources; mathematical skills; higher education